Negacyclic codes of length 4psover Fpm+uFpmand their duals - Hai Q. Dinh (2018)
© 2018 Elsevier B.V. For any odd prime p, negacyclic codes of length 4psover the finite commutative chain ring Fpm+uFpmare investigated. The algebraic structures of such codes are classified and completely determined. As an application, the number of codewords and the dual of each negacyclic code are obtained. Simpler structure of cyclic codes of length 4psover Fpm+uFpmis also noted. Among others, some self-dual negacyclic and cyclic codes of length 4psover Fpm+uFpmare provided.